John Maynard Keynes and Ludwig von Mises on Probability - Van Den Hauwe, Ludwig (2018)
As regards the views about probability of Ludwig von Mises, it is undeniably true that these display considerable nuance and that they can be considered as being of a sui generis variety. Even if Ludwig von Mises’s views on probability exhibit a closer conceptual affinity with Keynes’s philosophy of probability than with the frequency interpretation espoused by his brother Richard von Mises, an important difference between the views of Ludwig von Mises and those of John Maynard Keynes in this respect will nevertheless be acknowledged.